1997
DOI: 10.1258/002367797780600224
|View full text |Cite
|
Sign up to set email alerts
|

Experimental pneumonia virus of mice infection of guineapigs spontaneously infected with Bordetella bronchiseptica

Abstract: SummaryGuineapigs that were intranasally inoculated with pneumonia virus of mice (PVM) seroconverted to PVM by 11 days post-infection. During the course of study (2-60 days postinfection) no gross or histologic lesions were identified within the lungs that could be attributed to PVM infection. Mild rhinitis and tracheitis were found in most animals and acute purulent bronchopneumonia in two animals, which may have resulted from spontaneous subclinical Bordetella bronchiseptica infection. Viral and bacterial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…The results showed evidence of severe microbiological contamination, especially at facility A, the guinea pigs of which were positive for E. cuniculi, Sendai virus, PVM, and Reo-3 infections. Although most of these pathogens cause subclinical infections in guinea pigs [8], some were responsible for aggravating lesions by coinfection with other microorganisms [6,14]. Also, all of these pathogens have the ability to infect and cause various lesions in other laboratory animals including mice, rats, and rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed evidence of severe microbiological contamination, especially at facility A, the guinea pigs of which were positive for E. cuniculi, Sendai virus, PVM, and Reo-3 infections. Although most of these pathogens cause subclinical infections in guinea pigs [8], some were responsible for aggravating lesions by coinfection with other microorganisms [6,14]. Also, all of these pathogens have the ability to infect and cause various lesions in other laboratory animals including mice, rats, and rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Growth in vitro is best at 30°C but is slow to poor at 37°C, with minute, circular, pearlescent colonies present at 24 h and maximum-sized colonies apparent at 72 h. Colonies embed in the media and are surrounded variably by a zone of β-hemolysis Brabb et al, 2012). The organism variably dissociates in culture (isogenic mutation), and these isolates vary in hemolysin, dermonecrotoxin, proteases, adenylate cyclase, and hemagglutinin production, which may affect host specificity, virulence, and disease manifestation (Griffith et al, 1996). Restriction enzyme analysis of chromosomal DNA demonstrated that diversity among isolates was striking even within a host species (Sacco et al, 2000).…”
Section: A Bordetella Bronchisepticamentioning
confidence: 99%
“…Seropositive reactions to PVM have been seen historically in guinea pig colonies in animals without apparent disease (Van Hoosier and Robinette, 1976). Inoculation of guinea pigs with a strain of PVM that caused mortality in immunocompetent and immunodeficient mice resulted in no clinical signs, although the guinea pigs seroconverted within 11 days after inoculation (Griffith et al, 1997).…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%